ICT Critical Infrastructures and Society 10th IFIP TC 9 International Conference on Human Choice and Computers, HCC10 2012, Amsterdam, The Netherlands, September 27-28, 2012. Proceedings - Hercheui, Magda David; Whitehouse, Diane; McIver, William; Phahlamohlaka, Jackie; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 10th IFIP TC 9 International Conference on Human Choice and Computers, HCC10 2012, held in Amsterdam, The Netherlands, in September 2012. The 37 revised full papers presented were carefully reviewed and selected for inclusion in the volume. The papers are organized in topical sections on national and international policies, sustainable and responsible innovation, ICT for peace and war, and citizens' involvement, citizens' rights and ICT.
National and International Policies -- Sustainable and Responsible Innovation -- ICT for Peace and War -- Citizens$1 (BInvolvement, Citizens$1 (BRights and ICT.s
Keywords: Computer science; Data protection; Information systems; Information Systems; Computer Science; Computers and Society; e-Commerce/e-business.; Systems and Data Security; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl. Internet).; Management of Computing and Information Systems